CSR projects: a collaboration project with Serba Dinamik Sdn Bhd for the production of hand sanitizer - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2020)
This hand sanitizer project was led by Prof. Dr. Chan Chin Han in collaboration with Serba Dinamik Sdn. Bhd. The project, which was fully sponsored by the company, was carried out at Biology Laboratory A402 with the involvement of three FSG laboratory staff. They successfully produced a total of 1,200 bottles of 50 ml hand sanitizers within a week. The hand sanitizers were then distributed to frontliners throughout the period of the Movement Control Order.